AUDIT MANAJEMEN SDM DI SDN 145 BANCA: REKRUTMEN, PENGEMBANGAN, SUPERVISI, EVALUASI, DAN ETIKA PROFESI GURU - Nur Izza; Suardi; Idawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The urgency of this research stems from the need for elementary schools to ensure that teacher management is effective, accountable, and aligned with the demands of today's educational professionalism. This research was conducted to audit human resource management at SD Negeri 145 Banca, focusing on the teacher recruitment and placement process, professional development, academic supervision, performance evaluation, and the implementation of professional ethics. The research used a Mixed Methods approach with an Explanatory sequential design using interview, observation, document study, and teacher questionnaire techniques. The sample was selected using purposive sampling for interviews and total sampling for questionnaires. The first step was to analyze the quantitative results of the teacher questionnaires, then explained through qualitative data. The research findings indicate that human resource management in the school has been running well, especially in the aspects of teacher development and implementation of the code of ethics. The questionnaire findings with an average score of 96.7% indicate a Very Strong category, indicating that teachers have a high commitment to participating in training, implementing the code of ethics, receiving supervision, and demonstrating motivation to develop professionalism. However, it still requires strengthening in the distribution of coaching and optimization of teacher duties. The novelty of this research lies in its comprehensive audit, which integrates recruitment, development, supervision, evaluation, and professional ethics. Its contribution is providing a comprehensive overview that can serve as a reference for policies to improve the quality of teaching staff management in elementary schools.